Drug-induced thyroid disorders - (:unkn) unknown (AVES PRESS LTD, 2015)
Drugs cure the diseases, but sometimes adverse effects occur and these adverse effects may cause new diseases. Drug-induced diseases include drug-induced thyroid disorders. The studies show that there are few agents implicated in drug-induced thyroid disorders, especially amiodarone, lithium and interferons, and that these agents can lead to significant consequences or these effects may not be important. Drugs induce adverse effects via various mechanisms. They may affect thyroid hormone synthesis, release, function or regulation. When adverse effects occur, minimizing or discontinuation of the suspected drug or addition of a new drug may be required. Particularly in patients at risk should be educated on signs and symptoms of drug-induced thyroid disorders. If they experience these signs and symptoms they should be advised to admit to a hospital.
Keywords: Drug; hyperthyroidism; hypothyroidism